Formal Methods in Architecture Proceedings of the 5th International Symposium on Formal Methods in Architecture (5FMA), Lisbon 2020 - Eloy, S.; Viana, D. L.; Morais, F.; Vaz, J. V. (2021)
This edited book gathers research studies presented at the 5th International Symposium on Formal Methods in Architecture (5FMA), Lisbon 2020. Studies focus on the use of methodologies, especially those that have witnessed recent developments, that stem from the mathematical and computer sciences and are developed in a collaborative way with architecture and related fields. This book constitutes a contribution to the debate and to the introduction of new methodologies and tools in the mentioned fields that derive from the application of formal methods in the creation of new explicit languages for problem-solving in architecture and urbanism. It adds valuable insight into the development of new practices solving identified societal problems and promoting the digital transformation of institutions in the mentioned fields. The primary audience of this book will be from the fields of architecture, urban planning, civil engineering, AEC, landscape design, computer sciences and mathematics, both academicians and professionals.